MALADAPTIVE PARENTING AND PEER GROUP BULLYING AS PATHOLOGICAL PATHWAYS TO BORDERLINE PERSONALITY DISORDER SYMPTOMS IN EARLY ADULT: CASE REPORT - Hayuning Widhihutami; Zuhrotun Ulya (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2023)
Introduction – Maladaptive experiences during adolescene have been consistently linked with borderline personality disorder. BPD is a serious mental illness characterized by pervasive pattern of instability in affect regulation, impulse control, interpersonal relationships, and self-image. Tthere was an interrelated relationship between parenting experiences and the development of BPD symptoms. Children who reported chronic bullying had a fivefold increase in the likelihood of developing BPD symptoms. Methods – Presented the case of patient, 20 years old young male with symptoms of borderline personality disorder turned out to have maladaptive parenting and history of became victim by peer group bullying since childhood. Data were taken from interviews and mental status examinations in psychiatric clinics, then a literature review was carried out. Results – The development of borderline personality disorder in adult linked with report of low care parenting, involves coldness, indifference, and rejection. BPD is also inevitable from hereditary risk factors. Discuss – There is a direct significant association between being victim of bullying and development of BPD. Empathy is one important aspect of social behavior that may not function in BPD. Atypical depressed patients with affective dysregulation first diagnosed with borderline personality disorder if do not meet the diagnostic criteria for bipolar disorder. Conclusion – Borderline personality disorder (BPD) is very prone to occur in young adults. Starting from affect dysregulation, inability to impulse control, unstable interpersonal relationships, and unstable self-image that begin to develop in children and adolescents when exposed to environmental risk factors. Risk factors that are very often influencing are family and peer group relationships. BPD is also an entry point for developing into bipolar disorder. Therefore, effective interventions should be targeted, early preventing the development of affect dysregulation in the development of the borderline personality disorder by reducing exposure to environmental risk factors. Keywords: borderline personality disorder, maladaptive parenting, bullying.